HUBUNGAN TINGKAT PENGETAHUAN PERAWAT DENGAN KEPATUHAN MELAKSANAKAN PENDOKUMENTASIAN ASKEP DI RUANG RAWAT INAP RS JIH YOGYAKARTA - Widuri Widuri; Maryadi Maryadi; Lestari Dwi Astuti (STIKES Wira Husada Yogyakarta, 2017)
Background: Activity of nursing is one of activity servicing in hospital, role to give nursing care which is conduct assesment to need of patiens, planning nursing, conduct plan of nursing, evaluate nursing, and conduct documentation of nursing care. Documentation of nursing care is the display of nurse performer in conduct the nursing care. Quality of documentation of nursing care can be seen from completeness and accuracy in writing of nursing process.Objectivity: To know the relationship between the levels knowledge of nurse with the obedience to documentation of nursing care in inpatient unit of JIH.Method of research: the research use cross sectional method. Instruments in the research use questionnaire and the observation of medical record. Taking the sample in the research is total sampling there 87 respondents. Processing the data use rank spearman correlation test.Result: The result of relationship between the level knowledge of nurse with the obedience to conduct documentation of nursing care is significant with p-value is 0,000 and (r 0,371).Conclusion: There are closely weak relation between the level of knowledge with obedience of nurse to conduct documentation of nursing care in inpatient of JIH Yogyakarta with the relationship is weak.